Proactive Personality & Employee Creativity: The Role of Organizational Learning Culture as Mediator - Karina A. H. Putri; Arum Etikariena (Budapest International Research and Critics University, 2021)
This study aims to determine the role of organizational learning culture on the relationship between proactive personality and employee creativity. The study uses a self-report online survey that was distributed to 158 employees in a company engaged in the construction and repair of network infrastructure in Indonesia. The data analysis technique used Hayes PROCESS Model 4 (Mediator Regression Analysis). The results of the research through the perspective of person-fit theory show that employees with a high level of proactive personality will have a high level of creativity, and will increase when employees are in an organizational learning culture. Organizational learning culture is considered to have a positive influence on employee creativity. Organizations need to consider implementation in increasing creativity through organizational learning culture.